2017
DOI: 10.1089/nat.2016.0641
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Distribution and Nuclear Activity of Antisense Oligonucleotides After Unassisted Uptake in Myoblasts and Differentiated MyotubesIn Vitro

Abstract: Clinical efficacy of antisense oligonucleotides (AONs) for the treatment of neuromuscular disorders depends on efficient cellular uptake and proper intracellular routing to the target. Selection of AONs with highest in vitro efficiencies is usually based on chemical or physical methods for forced cellular delivery. Since these methods largely bypass existing natural mechanisms for membrane passage and intracellular trafficking, spontaneous uptake and distribution of AONs in cells are still poorly understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…At present, most studies on intracellular presence and trafficking rely on covalent attachment of a fluorophore onto the oligonucleotide [38][39][40][41][42][43]. These studies involving fluorescently labeled oligonucleotides are beneficial to understanding the distribution, and some constructs mimic very well the situation of unconjugated AON [44].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most studies on intracellular presence and trafficking rely on covalent attachment of a fluorophore onto the oligonucleotide [38][39][40][41][42][43]. These studies involving fluorescently labeled oligonucleotides are beneficial to understanding the distribution, and some constructs mimic very well the situation of unconjugated AON [44].…”
Section: Introductionmentioning
confidence: 99%
“…Neither for R9-nor for gymnotically delivered ASOs did we observe such a localization. This was surprising, as in a previous study we had described nuclear localization and efficacy of gymnotically delivered ASOs, but this discrepancy can be explained by the much longer incubation times used earlier, as well as intrinsic differences between murine and human myoblasts (44). Fluorimetry on cell lysates further showed that the uptake of ASOs was more than 10-fold higher in cells that were incubated with PF14 polyplexes compared with R9 polyplexes or naked ASOs, which is in agreement with a previous report (32).…”
Section: Discussionmentioning
confidence: 66%
“…Thus, areas that showed highly fluorescent spots from other focal planes than the nucleus were distinguished from those nuclei that had a homogeneous fluorescence distribution. For each of the 3 independent uptake experiments, between 57 and 103 nuclei were measured (untreated control [38][39][40][41][42][43][44][45][46][47][48]. A 1-way ANOVA was performed to test whether there was a treatment effect.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…However, immunofluorescence must be performed on fixed and permeabilized cells in order to deliver the antibodies to the interior of the cell. Oligonucleotides and other biomolecules have been shown to redistribute throughout the cell as a result of fixation, leading to false-positive artifacts ( 33 , 51 , 86 , 108 , 109 ). Finally, even with careful colocalization studies, it can be difficult to deconvolute cytosolic versus endosomal material in a definitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with the RNA therapeutic, cells were fixed and permeabilized prior to staining with antibodies against specific endocytic markers. As several studies have shown ( 33 , 51 , 86 , 108 , 109 ), fixation can allow for redistribution of oligonucleotides and other biomolecules during subsequent incubation steps. When investigating subcellular localization, it is inherently problematic to interpret results from fixed and permeabilized cells.…”
Section: Discussionmentioning
confidence: 99%